The effects of exercise stress testing, diurnal variation and temporal decline on circulating progenitor cells - Watson, Timothy; Shantsila, Eduard; Karthikeyan, Vellore J.; Jessani, Shahirose; Goon, Patrick K.; Lip, Gregory Y. H. (Thrombosis and Haemostasis, 2010)
Endothelial damage/dysfunction is involved in numerous cardiovascular disease processes. Given that the mature endothelial cells have limited capacity for self regeneration, circulating progenitor cells (CPCs) may modulate the balance between vascular damage and regeneration. The three aims of the present study were 1) to define the influence of exercise treadmill testing (ETT) on peripheral CPC levels; 2) to assess the diurnal variation of CPC counts; and 3) to investigate the rate of temporal decline in CPCs once ex vivo. The dynamics of CPC count changes following an ETT were assessed on consecutive 20 patients referred to our ‘rapid-access’ chest pain clinic (70% male, age 69.9 ± 7.8) with venous blood samples taken pre-exercise, immediately post-exercise and at 30 minutes post-exercise. Diurnal variation in CPCs was assessed in 13 stable in-hospital patients (46% male, age 69.1 ± 7.5 years) with blood samples were taken five times every 6 hours. To investigate the temporal decline, blood samples from 12 patients (58.3% male, age 69.9 ± 7.9 years) were reprocessed for CPC counts at 4 hours and at 24 hours after sample collection. Plasma levels of von Willebrand factor (vWf) and soluble E-selectin (sE-selectin) were assessed by ELISA. CPCs were enumerated with flow cytometry as CD34+, CD133+, CD45dim events. Exercise led to significant increases in vWF and sE-selectin levels, but no significant influence on CPC counts were observed. Baseline CPC numbers demonstrated a negative correlation with vWf (r=-0.551, p=0.012) and sE-selectin levels (r=-0.494, p=0.027). CPC counts showed a significant diurnal variation, being significantly higher at 12 a.m. compared to 12 p.m. (p=0.046) and 6 p.m. (p=0.023). A 4 hour delay in sample preparation did not affect CPCs counts, but there was a significant decline in CPC recovery when sample processing was delayed by 24 hours (p<0.05). Routine exercise stress testing does not significantly affect CPC counts. Peripheral CPC levels showed a significant diurnal variation. Delays in sample preparation for CPC counts should be avoided as they may influence the accuracy of the test by resulting in a significant decline in CPC recovery. Thus, various factors may affect accuracy of CPC enumeration that may limit their role as a reliable clinical marker and biomarker of endothelial damage.
Keywords: Circulating progenitor cells; endothelial dysfunction; vascular biology; exercise stress testing; temporal decline; diurnal variation